Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2017)
In the middle of 2017, global activity is firming broadly as expected. Manufacturing and trade are picking up, confidence is improving and international financing conditions remain benign. Global growth is projected to strengthen to 2.7 percent in 2017 and 2.9 percent in 2018-19, in line with OECD January forecasts. In emerging market and developing economies (EMDEs), growth is predicted to recover to 4.1 percent in 2017 and reach an average of 4.6 percent in 2018-19, as obstacles to growth in commodity exporters diminish, while activity in commodity importers continues to be robust. Risks to the global outlook remain tilted to the downside. These include increased trade protectionism, elevated economic policy uncertainty, the possibility of financial market disruptions, and, over the longer term, weaker potential growth. .....